If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(w + 5) = 9w + 23 Reorder the terms: 7(5 + w) = 9w + 23 (5 * 7 + w * 7) = 9w + 23 (35 + 7w) = 9w + 23 Reorder the terms: 35 + 7w = 23 + 9w Solving 35 + 7w = 23 + 9w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-9w' to each side of the equation. 35 + 7w + -9w = 23 + 9w + -9w Combine like terms: 7w + -9w = -2w 35 + -2w = 23 + 9w + -9w Combine like terms: 9w + -9w = 0 35 + -2w = 23 + 0 35 + -2w = 23 Add '-35' to each side of the equation. 35 + -35 + -2w = 23 + -35 Combine like terms: 35 + -35 = 0 0 + -2w = 23 + -35 -2w = 23 + -35 Combine like terms: 23 + -35 = -12 -2w = -12 Divide each side by '-2'. w = 6 Simplifying w = 6
| 3(5-2n)=7n-24 | | (3x-5)(x^2-6x+4)= | | -14=3w-8 | | 35x^2+x-12=0 | | 5y+2x=410 | | y-3/y^2-y+3/2y | | 35x+100=415 | | 2x+5y=410 | | -12b+4=52 | | 3211=16t^2 | | x(2)-x^2-5x-25=0 | | 2x+7x+10=0 | | 3=7n+6-3 | | (8x+9y)(8x-9y)= | | x/2+3x/4=-9 | | 6d+7=19 | | 24w^6+24w^3=0 | | 11X-2=72 | | 5-p=20 | | 3=m-[-2] | | 6x+2(-4x-16)=-54 | | -64-25-9= | | 14=-7a | | xy-4y=21996 | | X=-3-13x | | 12000=.8(v)-.08(v)(6) | | (20x^2+23x-7)/x-1 | | (X-6)=-12 | | -9=15v/3 | | 1/2x+1+3/4=-9 | | -3(2x+5)=-27 | | 17-6xn=47+10xn |